The Term "can" In General & Special Criminal Offenses Based on Principles, Theories, and Criminal Law Doctrines - Youngky Fernando (Law Doctoral Community Service Journal, 2023)
The term â€œcanâ€ is a legal term often used in relation to general offenses and specific offenses in criminal law. In the context of general offenses, the term â€œcanâ€ refer to the authority or power delegated to authorized officials to take criminal actions. The purpose of this study is to discuss the phrase â€œcanâ€ in general and specific offenses based on principles, theories, and doctrines of criminal law. The research method used is normative legal research, utilizing primary, secondary, and tertiary legal materials, through a legislative approach.